Machine Learning and Data Mining in Pattern Recognition 8th International Conference, MLDM 2012, Berlin, Germany, July 13-20, 2012. Proceedings - Perner, Petra; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 8th International Conference, MLDM 2012, held in Berlin, Germany in July 2012. The 51 revised full papers presented were carefully reviewed and selected from 212 submissions. The topics range from theoretical topics for classification, clustering, association rule and pattern mining to specific data mining methods for the different multimedia data types such as image mining, text mining, video mining and web mining.
Keywords: Computer science; Database management; Data mining; Artificial intelligence; Computer vision; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Mathematical Logic and Formal Languages; Database Management; Data Mining and Knowledge Discovery; Pattern Recognition; Image Processing and Computer Vision